2004
DOI: 10.1021/es049044o
|View full text |Cite
|
Sign up to set email alerts
|

Mass Budget of Perfluorooctane Surfactants in Lake Ontario

Abstract: Perfluorooctane surfactants have been reported in biota, water, and air samples worldwide. Despite these reports, the main environmental sources of these compounds remain undefined. To address this gap in knowledge, an annual lakewide mass budget of eight perfluorooctane surfactants was developed for Lake Ontario. To determine the atmospheric contribution to the mass budget, over-the-lake gasphase air concentrations for N-EtFOSE and N-EtFOSA and particulate-phase air concentrations for PFOS in any air sample a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
43
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(49 citation statements)
references
References 20 publications
3
43
0
1
Order By: Relevance
“…Minor modifications of this solvent-based method have thereafter been widely used to investigate airborne concentrations of polyfluorinated substances in e.g. the Arctic atmosphere [20], USA [21], Asia [22], industrialized and remote areas in Central Europe and less urbanized regions in the Southern Hemisphere [9]. Similar passive air sampler comprising of XAD-4 adsorbent impregnated in PUF disk has also been developed [23].…”
Section: Introductionmentioning
confidence: 99%
“…Minor modifications of this solvent-based method have thereafter been widely used to investigate airborne concentrations of polyfluorinated substances in e.g. the Arctic atmosphere [20], USA [21], Asia [22], industrialized and remote areas in Central Europe and less urbanized regions in the Southern Hemisphere [9]. Similar passive air sampler comprising of XAD-4 adsorbent impregnated in PUF disk has also been developed [23].…”
Section: Introductionmentioning
confidence: 99%
“…It has been assumed that the contaminated wastewaters from domestic, commercial, or industrial areas may be one of the principal and significant potential sources of PFCs [14,15]. WWTPs are believed as a major source of PFCs to natural waters.…”
Section: Introductionmentioning
confidence: 99%
“…WWTPs are believed as a major source of PFCs to natural waters. Boulanger et al reported that WWTP effluent was the largest source of PFCs discharged into the Lake Ontario [15]. Murakami et al also proposed that most PFCs in surface waters during dry weather are derived from wastewater and manufacturing effluents [16].…”
Section: Introductionmentioning
confidence: 99%
“…Another study of concentrations and mass fluxes of TFA in aquatic systems from Switzerland also ignored sediment partitioning and soil retention. [74] PFA losses to sediments were also ignored in a mass balance of these compounds in Lake Ontario, [149] but a subsequent analysis of potential sorption sensitivity towards this assumption was shown to likely be valid under the site specific conditions. [106] However, sedimentation rates in mostly oligotrophic lakes such as Lake Ontario (http://www.epa.gov/glnpo/glindicators/water/trophica.html) are expected to be much lower than in more eutrophic systems and/or lakes with large sediment inputs (such as behind hydroelectric dams).…”
mentioning
confidence: 99%